A compression transmission device for the evaluation of bonding strength of biocompatible microfluidic and biochip materials and systems - Kratz, S. R. A. (Sci Rep, 2020)
Bonding of a variety of inorganic and organic polymers as multi-layered structures is one of the main challenges for biochip production even to date, since the chemical nature of these materials often does not allow easy and straight forward bonding and proper sealing. After selection of an appropriate method to bond the chosen materials to form a complex biochip, function and stability of bonding either requires qualitative burst tests or expensive mechanical multi-test stations, that often do not have the right adaptors to clamp biochip slides without destruction. Therefore, we have developed a simple and inexpensive bonding test based on 3D printed transmission elements that translate compressive forces via manual compression, hand press or hydraulic press compression into shear and tensile force. Mechanical stress simulations showed that design of the bonding geometry and size must be considered for bonding tests since the stress distribution thus bonding strength heavily varies with size but also with geometry. We demonstrate the broad applicability of our 3D printed bonding test system by testing the most frequent bonding strategies in combination with the respective most frequently used biochip material in a force-to-failure study. All evaluated materials are biocompatible and used in cell-based biochip devices. This study is evaluating state-of-the-art bonding approaches used for sealing of microfluidic biochips including adhesive bonding, plasma bonding, solvent bonding as well as bonding mediated by amino-silane monolayers or even functional thiol-ene epoxy biochip materials that obviate intermediate adhesive layers.